ETIKA BISNIS ISLAM DAN KEADILAN DISTRIBUTIF: TINJAUAN FILOSIFIS TERHADAP EKSPLOITASI HARGASAAT DARURAT BENCANA - Ridha, Muhammad (HEI EMA : Jurnal Riset Hukum, Ekonomi Islam, Ekonomi, Manajemen dan Akuntansi, 2026)
The practice of unnaturally increasing the price of basic necessities during a disaster is an economic phenomenon that often occurs in Indonesia. This research aims to analyze the practice from the perspective of Islamic law, especially through the concepts of ihtikar (hoarding) and tas'ir (pricing). Using qualitative research methods with a juridical-normative approach, this study evaluates how Islamic economic morality responds to market exploitation in the midst of a humanitarian crisis. The results of the study show that the price increase driven by the motive of speculation and the use of legal emergency conditions is haram, because it violates the principle of la darar wa la dirar (not to harm oneself and others). Although under normal conditions the price is determined by the market mechanism, the state has the authority to intervene in prices (tas'ir) to protect the public interest (maslahah mursalah) when there is a market distortion due to a disaster. This article concludes that the enforcement of Islamic business ethics is not only a matter of formal legality, but also about maintaining a balance between the rights of individual traders and the right of life of the masses. This research contributes to strengthening market regulation based on human values and distributive justice in sharia economic law.